Subcutaneous ω-Conotoxins Alleviate Mechanical Pain in Rodent Models of Acute Peripheral Neuropathy - Md. Mahadhi Hasan; Hana Starobova; Alexander Mueller; Irina Vetter; Richard J. Lewis (Marine Drugs, 2021)
The peripheral effects of ω-conotoxins, selective blockers of N-type voltage-gated calcium channels (CaV2.2), have not been characterised across different clinically relevant pain models. This study examines the effects of locally administered ω-conotoxin MVIIA, GVIA, and CVIF on mechanical and thermal paw withdrawal threshold (PWT) in postsurgical pain (PSP), cisplatin-induced neuropathy (CisIPN), and oxaliplatin-induced neuropathy (OIPN) rodent models. Intraplantar injection of 300, 100 and 30 nM MVIIA significantly (p < 0.0001, p < 0.0001, and p < 0.05, respectively) alleviated mechanical allodynia of mice in PSP model compared to vehicle control group. Similarly, intraplantar injection of 300, 100, and 30 nM MVIIA (p < 0.0001, p < 0.01, and p < 0.05, respectively), and 300 nM and 100 nM GVIA (p < 0.0001 and p < 0.05, respectively) significantly increased mechanical thresholds of mice in OIPN model. The ED50 of GVIA and MVIIA in OIPN was found to be 1.8 pmol/paw and 0.8 pmol/paw, respectively. However, none of the ω-conotoxins were effective in a mouse model of CisIPN. The intraplantar administration of 300 nM GVIA, MVIIA, and CVIF did not cause any locomotor side effects. The intraplantar administration of MVIIA can alleviate incision-induced mechanical allodynia, and GVIA and MVIIA effectively reduce OIPN associated mechanical pain, without locomotor side effects, in rodent models. In contrast, CVIF was inactive in these pain models, suggesting it is unable to block a subset of N-type voltage-gated calcium channels associated with nociceptors in the skin.